2020
DOI: 10.1186/s12893-020-00796-7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of perforated peptic ulcer disease patient in four teaching hospitals in Addis Ababa, Ethiopia: a prospective cohort multicenter study

Abstract: Background: Perforated peptic ulcer disease is a surgical emergency with a high morbidity and mortality. The socio-demographic characteristic and the factors associated with morbidity and mortality seems to differ between the developed and developing world. This is the first a prospective cohort study in Ethiopia designed to analyze pattern and outcome of patients with perforated peptic ulcer disease in four teaching hospitals affiliated with SOM, CHS of Addis Ababa University. Method: This is a prospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Positive previous history of peptic dyspepsia was observed in nearly half (25 (49%)) of the patients with peptic ulcer, this might explain the inaccessibility of good health facilities, and most of them may encounter non-professional health workers and traditional healers in many parts of the regions, and patient will seek proper health care facility when condition gets worse and patient develops severe abdominal pain and peritonism. This finding is common in developing countries as several reports stated [ 8 , 10 , 13 ].…”
Section: Discussionmentioning
confidence: 53%
“…Positive previous history of peptic dyspepsia was observed in nearly half (25 (49%)) of the patients with peptic ulcer, this might explain the inaccessibility of good health facilities, and most of them may encounter non-professional health workers and traditional healers in many parts of the regions, and patient will seek proper health care facility when condition gets worse and patient develops severe abdominal pain and peritonism. This finding is common in developing countries as several reports stated [ 8 , 10 , 13 ].…”
Section: Discussionmentioning
confidence: 53%
“…NSAIDs use rates in these areas were significantly lower than those in developed countries [35,36]. Studies have also shown that the rates of severe PUD-related complications, such as perforation of the digestive tract, are high in these countries and territories and appear to be associated with Khat intake [37]. When stratified by SDI, the incidence of PUD showed decreasing trends in different groups over time.…”
Section: Discussionmentioning
confidence: 89%
“…All the patients in our study generally describe a sudden and severe epigastric pain on admission, this pain being localized early on and then spreading rapidly to the abdomen 19 . In a study by Lau et al; showed that patients usually present with severe, sudden upper abdominal pain that is localized initially and then spreading rapidly [20][21] In this study, death occurred in 13 patients which was quite an acceptable mortality rate compared to other literature data 22 . Most of the patients died in the first week after surgery, on average after 4 days.…”
Section: Discussionmentioning
confidence: 49%